Nighttime caffeine intake increases motor impulsivity - Erick Benjamin Saldes; Paul Rafael Sabandal; Kyung-An Han (iScience)
Summary: Caffeine is commonly consumed at night by shift workers and military personnel to promote alertness, yet its adverse effects remain underexplored. Here, we show that nighttime caffeine intake impairs inhibitory control in Drosophila melanogaster, resulting in impulsive motor behavior, with females more sensitive than males. This effect is independent of hyperactivity or sleep loss, as walking speed was unchanged and artificial sleep deprivation via light or mechanical stimulation did not elicit similar deficits. Notably, daytime caffeine intake did not impair inhibitory control, highlighting a circadian gating of caffeine’s impact. Mechanistically, we show that dopamine signaling mediates this effect. Reduced dopamine synthesis, silencing of protocerebral anterior medial (PAM) dopaminergic neurons, or altered dopamine transporter activity attenuated or exacerbated impulsivity. Targeted manipulations identified the dopamine D1 receptor (dDA1/Dop1R1) in the mushroom body (MB) α/β and γ lobes as essential for this effect, with γ-lobe neurons exhibiting heightened sensitivity. These findings uncover a circadian- and dopamine-dependent mechanism.